PENGARUH KONSENTRASI ETANOL TERHADAP TOTAL FENOLIK DAN FLAVONOID SERTA AKTIVITAS ANTIOKSIDAN DARI DAUN KUNYIT (Curcuma longa L.) DENGAN METODE ABTS - Nurcahyani, Dona Agustin; Raharjo, Danang; Apriliawan, Hidayah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Turmeric's leaves possess the greatest antioxidant potential. Therefore, further utilization of flavonoid and phenolic compounds is necessary as antioxidants and to enhance their bioactivity as a medicine. This study aimed to determine the effect of ethanol concentration on total phenolic content using the Folin-Ciocalteau analysis method while total flavonoid content using the AlCl₃ analysis method and antioxidant activity of turmeric leaves using the ABTS method, The research design used was experimental research. The results obtained were ethanol concentrations of 50%, 70% and 96%, The results showed that 70% ethanol extract had the highest phenolic content with an average of (63.77 ± 0.40 mg GAE / g), and 70% ethanol extract had the highest flavonoid content with an average of (22.88 ± 0.5 mg QE / g). However, the strongest antioxidant activity was shown by 96% ethanol extract with an IC₅₀ value of (46.36 ± 1.15 ppm (<50 ppm). Thus, turmeric leaf extract with 96% ethanol solvent had the strongest antioxidant activity, while 70% ethanol produced the highest phenolic and flavonoid levels.